Line 16: Line 16:
 
----
 
----
 
===Answer 1===
 
===Answer 1===
'''trigonometric identities'''
+
:'''trigonometric identities'''
  
:By trigonometric identities(which can be proof by Eular's equations easily):
+
::By trigonometric identities(which can be proof by Eular's equations easily):
:<math>cos(\alpha+\beta) = cos(\alpha)cos(\beta) -  sin(\alpha)sin(\beta)</math>
+
::<math>cos(\alpha+\beta) = cos(\alpha)cos(\beta) -  sin(\alpha)sin(\beta)</math>
  
'''Proof of separability'''
+
:'''Proof of separability'''
  
:<math>
+
::<math>
 
\begin{align}
 
\begin{align}
 
DSFT(f(m) \cdot g(n)) &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m) \cdot g(n) e^{-j(mu + nv)}\\
 
DSFT(f(m) \cdot g(n)) &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m) \cdot g(n) e^{-j(mu + nv)}\\
Line 29: Line 29:
 
&= F(u) \cdot G(v)
 
&= F(u) \cdot G(v)
 
\end{align}</math>
 
\end{align}</math>
:where
+
::where
:<math>F(u) =\sum_{m=-\infty}^{\infty} f(m) e^{-j(mu)} = DTFT(f(m))</math>
+
::<math>F(u) =\sum_{m=-\infty}^{\infty} f(m) e^{-j(mu)} = DTFT(f(m))</math>
:<math>G(v) =\sum_{n=-\infty}^{\infty} g(n) e^{-j(nv)} = DTFT(g(n))</math>
+
::<math>G(v) =\sum_{n=-\infty}^{\infty} g(n) e^{-j(nv)} = DTFT(g(n))</math>
  
'''Proof of linearity'''
+
:'''Proof of linearity'''
  
:<math>
+
::<math>
 
\begin{align}
 
\begin{align}
 
DSFT(f(m,n) + g(m,n)) &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} [f(m,n) + g(m,n)] e^{-j(mu + nv)}\\
 
DSFT(f(m,n) + g(m,n)) &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} [f(m,n) + g(m,n)] e^{-j(mu + nv)}\\
Line 41: Line 41:
 
&= F(u,v) + G(u,v)  
 
&= F(u,v) + G(u,v)  
 
\end{align}</math>
 
\end{align}</math>
:where
+
::where
:<math>F(u,v)  =\sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m,n) e^{-j(mu + nv)} = DSFT(f(m,n))</math>
+
::<math>F(u,v)  =\sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m,n) e^{-j(mu + nv)} = DSFT(f(m,n))</math>
:<math>G(u,v)  =\sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} g(m,n) e^{-j(mu + nv)} = DSFT(g(m,n))</math>
+
::<math>G(u,v)  =\sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} g(m,n) e^{-j(mu + nv)} = DSFT(g(m,n))</math>
  
'''DTFT:''' By computing DTFT or looking it up in the table, one can find
+
:'''DTFT:''' By computing DTFT or looking it up in the table, one can find
:<math>DTFT(cos(w_0n))=\pi[ \frac{}{}\delta(w-w_0)+\delta(w+w_0) ]</math>
+
::<math>DTFT(cos(w_0n))=\pi[ \frac{}{}\delta(w-w_0)+\delta(w+w_0) ]</math>
:<math>DTFT(sin(w_0n))=\frac{\pi}{j}[ \delta(w-w_0)-\delta(w+w_0) ]</math>
+
::<math>DTFT(sin(w_0n))=\frac{\pi}{j}[ \delta(w-w_0)-\delta(w+w_0) ]</math>
  
with all these tools we found, one can easily show the following:
+
:with all these tools we found, one can easily show the following:
  
:Let  
+
::Let  
:<math>\alpha = \frac{2\pi}{500}</math>
+
::<math>\alpha = \frac{2\pi}{500}</math>
:<math>\beta = \frac{2\pi}{200}</math>
+
::<math>\beta = \frac{2\pi}{200}</math>
  
:<math>
+
::<math>
 
\begin{align}
 
\begin{align}
 
DSFT&(\cos \left( 2 \pi  \left( \frac{m}{500}+ \frac{n}{200} \right) \right))\\
 
DSFT&(\cos \left( 2 \pi  \left( \frac{m}{500}+ \frac{n}{200} \right) \right))\\
Line 68: Line 68:
 
\end{align}</math>
 
\end{align}</math>
  
:where u and v repeats in every square with 2pi length.
+
::where u and v repeats in every square with 2pi length.
  
  

Revision as of 20:15, 19 November 2011

Practice Problem on Discrete-space Fourier transform computation

Compute the discrete-space Fourier transform of the following signal:

$ f[m,n]= \cos \left( 2 \pi \left( \frac{m}{500}+ \frac{n}{200} \right) \right) $

(Write enough intermediate steps to fully justify your answer.)


Share your answers below

You will receive feedback from your instructor and TA directly on this page. Other students are welcome to comment/discuss/point out mistakes/ask questions too!


Answer 1

trigonometric identities
By trigonometric identities(which can be proof by Eular's equations easily):
$ cos(\alpha+\beta) = cos(\alpha)cos(\beta) - sin(\alpha)sin(\beta) $
Proof of separability
$ \begin{align} DSFT(f(m) \cdot g(n)) &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m) \cdot g(n) e^{-j(mu + nv)}\\ &= \sum_{m=-\infty}^{\infty} f(m) e^{-j(mu)} \sum_{n=-\infty}^{\infty} g(n) e^{-j(nv)}\\ &= F(u) \cdot G(v) \end{align} $
where
$ F(u) =\sum_{m=-\infty}^{\infty} f(m) e^{-j(mu)} = DTFT(f(m)) $
$ G(v) =\sum_{n=-\infty}^{\infty} g(n) e^{-j(nv)} = DTFT(g(n)) $
Proof of linearity
$ \begin{align} DSFT(f(m,n) + g(m,n)) &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} [f(m,n) + g(m,n)] e^{-j(mu + nv)}\\ &= \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m,n) e^{-j(mu + nv)} + \sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} g(m,n) e^{-j(mu + nv)}\\ &= F(u,v) + G(u,v) \end{align} $
where
$ F(u,v) =\sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} f(m,n) e^{-j(mu + nv)} = DSFT(f(m,n)) $
$ G(u,v) =\sum_{m=-\infty}^{\infty} \sum_{n=-\infty}^{\infty} g(m,n) e^{-j(mu + nv)} = DSFT(g(m,n)) $
DTFT: By computing DTFT or looking it up in the table, one can find
$ DTFT(cos(w_0n))=\pi[ \frac{}{}\delta(w-w_0)+\delta(w+w_0) ] $
$ DTFT(sin(w_0n))=\frac{\pi}{j}[ \delta(w-w_0)-\delta(w+w_0) ] $
with all these tools we found, one can easily show the following:
Let
$ \alpha = \frac{2\pi}{500} $
$ \beta = \frac{2\pi}{200} $
$ \begin{align} DSFT&(\cos \left( 2 \pi \left( \frac{m}{500}+ \frac{n}{200} \right) \right))\\ &= DSFT[\cos \left( \alpha m + \beta n \right)] \\ &= DSFT[\cos(\alpha m)\cos(\beta n) - \sin(\alpha m)\sin(\beta n)]\\ &= DSFT[\cos(\alpha m)\cos(\beta n)] - DSFT[\sin(\alpha m)\sin(\beta n)]\\ &= DSFT[\cos(\alpha m)] \cdot DSFT[\cos(\beta n)] - DSFT[\sin(\alpha m)] \cdot DSFT[\sin(\beta n)]\\ &= \pi[ \delta(u-\alpha)+\delta(u+\alpha) ]\cdot\pi[ \delta(v-\beta)+\delta(v+\beta) ] + \frac{\pi}{j}[ \frac{}{}\delta(u-\alpha)-\delta(u+\alpha) ]\cdot\frac{\pi}{j}[ \frac{}{}\delta(v-\beta)-\delta(v+\beta) ]\\ &= \pi^2\{[ \delta(u-\alpha)+\delta(u+\alpha) ]\cdot[ \delta(v-\beta)+\delta(v+\beta) ] - [\delta(u-\alpha)-\delta(u+\alpha) ]\cdot[ \delta(v-\beta)-\delta(v+\beta) ]\}\\ &= 2\pi^2\{\delta(u-\alpha)\delta(v+\beta) + \delta(u+\alpha)\cdot\delta(v-\beta)\}\\ &= 2\pi^2\{\delta(u-\alpha,v+\beta) + \delta(u+\alpha,v-\beta)\}\\ \end{align} $
where u and v repeats in every square with 2pi length.


Answer 2

Write it here.


Back to ECE438 Fall 2011 Prof. Boutin

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett